Let's Keep Our Quality School Principals on the Job - Norton, M. Scott (The High School journal, 2002)
Research studies strongly support the fact that the leadership of the school principal impacts directly on the climate of the school and, in turn, on student achievement. National statistics relating to principal turnover and dwindling supplies of qualified replacements show clearly that principal turnover has reached crisis proportions. Increasing demands upon the work life of the principal, low salary levels, time constraints, lack of parent and community support and lack of respect are among the reasons that principals are leaving the position. It is essential that the principal's job description be reexamined and new strategies implemented in order to allow the principal to focus on teaching and learning. Specific recommendations for improving the current problem of principal turnover in schools are presented.